Antique sign - Lê Thái Hoàng Nguyên (22638911) (2025)
An original sign advertising reasonably priced coffee, pennywort drink and other refreshments. Artist Thuyên bought this from an antiques dealer. He believes it was made between 1975 and 1980 out of metal from a military aircraft.